Maintaining business during Covid-19 pandemic through social media: a content analysis of Indonesian Football Club Instagram account - Yosia Enggar Kurniawan; Deny Tri Ardianto; Andreas Slamet Widodo (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indonesia has become the largest football industry with a huge fan base. Football continues to become a profitable brand and generates extraordinary profits, considering that football has a wide and large market share. As a brand, many football clubs have realized the power of branding in marketing clubs outside the club's local market through branding strategies carried out into content on social media. Currently, social media has become a popular and effective new media in the branding strategy of a football club. Their Instagram account has gained millions of followers in recent years, creating an effective medium for sales and promotion. Many Indonesian big brands agree to sponsor the club as a way to promote their products as well. However, the global pandemic hit from March 2020 to August 2021, and there was a long hiatus for football matches, considering the branding activity of a football club is very dependent on the passing of matches in a competition. Football matches become the 'main product' that attracts the attention of fans and sponsors. Due to this catastrophe, how can football clubs in Indonesia maintain business during the COVID-19 pandemic through Instagram content? Using a semi-structured interview with internal parties of a big football club in Indonesia, this study generates some practical summaries and implications on how to maintain business during the COVID-19 pandemic. The result shows the significant influence of the COVID-19 pandemic on the content analysis of the Football Club in Indonesia through Instagram.